2006
DOI: 10.1051/animres:2006038
|View full text |Cite
|
Sign up to set email alerts
|

Walk and trot in the horse at driving: kinematic adaptation of its natural gaits

Abstract: -The walk and trot at hand and at driving of five Andalusian Purebred stallions were studied by a 2D semiautomatic analysis system. Linear, temporal and angular variables from the right fore and hind limbs were obtained by using a 2D kinematic analysis system. In order to identify significant differences between handled and driving gaits, a paired Student t-test was performed. The swing period and the stride lengths of both fore and hind limbs and the overreach distance were lower at driving. Stride durations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
8
1
1
Order By: Relevance
“…The angle range of motion was from 180 to 240 degrees, which indicated a flexion of the knee joint of about 60 degrees. This result was consistent with Miro et al (2006) and Hodson et al (2000). The curve of hoof acceleration showed two peaks, the first occurred at the breakover phase and the second peaks at the maximum displacement of the hoof.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The angle range of motion was from 180 to 240 degrees, which indicated a flexion of the knee joint of about 60 degrees. This result was consistent with Miro et al (2006) and Hodson et al (2000). The curve of hoof acceleration showed two peaks, the first occurred at the breakover phase and the second peaks at the maximum displacement of the hoof.…”
Section: Discussionsupporting
confidence: 89%
“…The stance phase of forelimb represented the 60% of the stride and the swing phase the 40%. Miro et al (2006) studied the stride duration of Andalusian horses walking overground, and the same behavior of phase's duration was observed. According to Duberstein et al (2013), a large swing-stance ratio is desirable for good quality movements.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This might be taken to imply that loading and type of load do not effect forelimb movement. These results are in accordance with the findings of Miró et al [10] who reported no significant differences between the ranges of motion of shoulder, elbow, and carpal joints when the horse was handled while walking or was cart-driven in the walking gait. However, based on the findings of this study, it is too early to state that the ponies are capable of maintaining their forelimb kinematic motion during EAT working because not every joint was monitored.…”
Section: Discussionsupporting
confidence: 93%
“…O tamanho amostral encontra-se de acordo com a metodologia empregada na experimentação com equinos nas áreas de treinamento e equitação (MIRÓ et al, 2006;WALDERN et al, 2009;LINDNER et al, 2010;CLAYTON et al, 2010;STUBBS et al, 2011a;CLAYTON et al, 2011). Para a inclusão no estudo, os animais foram avaliados clinicamente e considerados aptos caso não apresentassem sinais de alterações musculoesqueléticas.…”
Section: Methodsunclassified